It’s a Challenge, Not a Threat: Lecturers’ Satisfaction During the Covid-19 Summer Semester of 2020 - Feldhammer-Kahr, Martina; Tulis, Maria; Leen-Thomele, Eline; Dreisiebner, Stefan; Macher, Daniel; Arendasy, Martin; Paechter, Manuela (Frontiers in Psychology, 2021)
The summer semester had just begun at Austrian and German universities when Covid-19 was declared a global pandemic by the World Health Organization. Thus, in March 2020, all universities closed their campuses, switching to distance learning within the span of about a single day. How did lecturers handle the situation? Were they still able to turn the situation into a positive one? What were the main obstacles with this difficult situation, and where there conditions which helped them to overcome the new challenges? These are research questions of the present survey with a sample of 1,152 lecturers at universities in Austria and Germany. The survey focuses on the lecturers’ appraisals of the novel situation as challenging or threatful. These appraisals are important for approaching a situation or shying away from it. However, how well a person adjusts to a novel situation is also influenced by personal and environmental resources which help to overcome the situation. The present survey focused on four possible sources of influence: internal assessments of the situation determining it to be threatening and/or challenging, personal resources, attitudes, and support by the organization. It was investigated to which degree these sources of influence could contribute to the lecturers’ satisfaction (or dissatisfaction) with their teaching processes. A multiple regression with three criterion variables describing university lecturers’ perceived satisfaction with distance teaching was carried out. Predictor variables were the lecturers’ appraisals of challenge and threat, perceived support by the university and sense of belonging to the university, temporal resources, proficiency in using digital technologies, length of teaching experience, and gender. Lecturers were mostly satisfied with their teaching activities. Together with the perception of a low threat potential, challenge appraisals contributed strongest to satisfaction. In comparison, assessments of actual personal resources, skills in the use of digital technologies, teaching experience, and temporal resources were important but contributed less to satisfaction than challenge appraisals. It seems that lecturers were only able to use these resources when the technological resources were available and when the lecturers were confident in their technical abilities.